MUNICIPAL SOLID WASTE MANAGEMENT IN BEKASI CITY, INDONESIA AND KYOTO CITY, JAPAN - Ibrahim, . (Jurnal Ilmiah Administrasi Publik, 2015)
Municipal Solid Waste Management In Bekasi City, Indonesia And Kyoto City, Japan. The aim of this study is to describe and explore the current solid waste management in Bekasi City and uncover how this phenomenon impacts to the environment, economy and particularly the society. This study used a qualitative research, gathered data from both primary and secondary sources. Through field investigation and face-to-face interviews. The study found that in a day more than 1,600 tons of garbage is generated within the Bekasi municipality. With a population of 2.4 million, it means that one person contributes an average of 0.625 kg of garbage per day. Unfortunately, waste management service only coverage 53%, thus, 47% of garbage is indicated managed improperly. Several factors led this problem, on the economy aspect the problems were led by insufficient of Bekasi cityâs budget in running solid waste treatment. On social aspect due to by the lack of people awareness to maintain environmental cleanliness in public areas. This study also briefly describe waste history in Japan and garbage management in Kyoto City.